Administrative Penal Law Enforcement in Beauty Clinics: Unauthorized Use of Pharmaceuticals and Medical Devices in Indonesia - Marsya Intan Riani; Handoyo Prasetyo; Beniharmoni Harefa (PT. Multidisciplinary Press Indonesia, 2026)
The rapid growth of beauty clinics in Indonesia has raised significant legal concerns regarding the unauthorized use of pharmaceutical preparations and medical devices, including dermarollers. Although Indonesian health law provides administrative and criminal sanctions, enforcement mechanisms remain fragmented and inconsistently applied. This study examines the enforcement of administrative penal law in addressing unlawful practices in beauty clinics, particularly the misuse of pharmaceuticals and medical devices without proper authorization. This research employs a normative juridical method supported by statutory and case approaches. It analyzes relevant legislation, including health law and medical device regulations, as well as selected court decisions to evaluate how administrative and criminal sanctions are implemented in practice. The findings reveal that enforcement tends to prioritize criminal prosecution while administrative measures—such as license revocation, suspension, and regulatory supervision—are underutilized. This imbalance weakens preventive regulatory control and creates enforcement gaps. The study argues that effective health law enforcement requires an integrated administrative-penal framework that positions administrative sanctions as the primary preventive instrument, with criminal sanctions functioning as ultimum remedium. This research contributes to the development of administrative penal law theory within the context of health regulation and offers policy recommendations to strengthen regulatory coherence in Indonesia’s beauty clinic sector.